Services to library users with disabilities: Slide presentation for Benyalai Library, Thailand - Mohd Faizal, H.; Siti Juryiah, M.K. (2015)
Special Disable Users (SDU) is one of the category of users that uses the library at the University of Malaya Library (UML). According to Act 658, people with disabilities shall have the right to the access to information, communication and technology on equal basis with people without disabilities (Persons with Disabilities Act 2008, Act 685).The purpose of this article is to highlight all the initiatives led by the University of Malaya Library (UML) to improve the library services for the visually impaired and physically handicapped students and staffs registered as library members. This initiative was taken to support the mission and vision of the university to produce quality research and knowledgeable students. Special facilities and services should be developed to help this category of user to use the library. A survey was conducted by the UML to identify the efficiency of each service provided to engage the library services with that specific group. The result of the survey will be the guideline for UML to improve the library services provided for that particular user group. As a conclusion, it is important to ensure that UML can provide special library services concerning the specific user group, thus ensuring “a library for everyone”